A note on taxes, prices, wages, and welfare in general equilibirium models - Robinson, Sherman; Thierfelder, Karen (International Food Policy Research Institute, 1999)
Changes in real wages are often used to measure welfare changes. There is a problem, however, in interpreting measures of changes in factor returns when analyzing the impact of changes in taxes — such as tariffs and indirect taxes — that operate as wedges in product and factor markets versus direct taxes that do not work through the price system. One must account for both how the tax is collected and where the tax revenue goes. We sort out how a shift in tax structure will affect the real wage in a model which isolates the price, wage, revenue, and welfare effects. We start from a simple general equilibrium model which accounts for all income and expenditure flows in the economy and includes both traded and domestic goods. We analyze the impact of changes in indirect taxes and tariffs on prices and factor income and demonstrate the pitfalls of using real factor returns as a welfare indicator. There is a transfer effect on factor returns arising from any shift between indirect and direct taxes, regardless of any efficiency effects. Next, we add explicit factor markets to the model and describe the implications for income distribution in an extension of the Jones trade model. We find that the transfer effect dampens the magnification effect of a price change on factor returns, but does not reverse the Stolper-Samuelson results.